2013
DOI: 10.1097/mjt.0b013e31828900cb
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Acetaminophen

Abstract: Hospitals are subject to more economic pressures than ever before. On the one hand, cost containment or cost reduction is paramount, particularly in relation to costly branded pharmaceuticals. On the other hand, quality measures and value-based reimbursement penalizes poor patient care. Multimodal analgesia sits squarely in this quandary, since its very nature requires use of multiple drugs with their associated costs, though this approach has the potential to improve quality of care. We undertook a comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 48 publications
0
35
0
3
Order By: Relevance
“…In toxicological mechanism, APAP-induced hepatocellular impairment can be originated from its metabolite toxin of N-acetyl-p-benzoquinonimine which impairs to liver cells in turn [17-19]. In recent years, ever-increasing evidences have showed APAP induced visible liver injury as elucidated in proposed biological signaling pathways and molecular mechanisms [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…In toxicological mechanism, APAP-induced hepatocellular impairment can be originated from its metabolite toxin of N-acetyl-p-benzoquinonimine which impairs to liver cells in turn [17-19]. In recent years, ever-increasing evidences have showed APAP induced visible liver injury as elucidated in proposed biological signaling pathways and molecular mechanisms [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Indications for paracetamol administration were medical (traumatic delivery, necrotizing enterocolitis, prostaglandin E2 administration, fever) or surgical (eg, cardiac, thoracic, abdominal). Samples were collected in the first 48 hours after loading dose with a non-uniform non-sparse sampling scheme with a median (range) number of samples per individual of 7 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Subjects Of the Original Studiesmentioning
confidence: 99%
“…1 More recently, an intravenous formulation of paracetamol has become available, which was approved for use in term neonates, children and adults in Europe, even though the USFDA only approved its use for the treatment of acute pain and fever in adults and children aged 2 years and older. While intravenous paracetamol is now being used regularly as an analgesic in neonates, children and adults, 2,3 in the last few years, intravenous paracetamol in a dose as high as 60 mg/kg has also been proposed as an off-label treatment of patent ductus arteriosus in preterm neonates. [4][5][6] To derive evidence based dosing guidelines for intravenous paracetamol across age ranges including preterm neonates, term neonates, and infants, information is needed on its pharmacokinetics.…”
mentioning
confidence: 99%
“…Although not all studies of perioperative use of IV APAP have demonstrated reductions in opioid use and LOS, recent economic impact studies have shown reduced costs associated with IV APAP [26, 27]. These findings are supported by a pharmacoeconomic review of IV APAP, which concluded the body of evidence shows the drug has the potential to improve outcomes and hospital efficiency [28]. Up to an estimated 7% of patients who receive prescription opioids following surgery end up using these medications long-term [2933], which can result in tolerance, dependence, and addiction [34].…”
Section: Introductionmentioning
confidence: 99%